2018
DOI: 10.30637/2018.17-097
|View full text |Cite
|
Sign up to set email alerts
|

Koro syndrome : when culture interacts with psychopathology

Abstract: Koro syndrome is a psychiatric disorder specific to certain Asian cultures. It is characterized by acute and intense anxiety with fear of a retraction of the penis into the body and resultant death. We report the case of a 43-year-old Moroccan male presenting with persistent anxiety associated with avoidance behaviors and a chronic belief that his genitalia may shrink or disappear and lead to his death. This impacted his professional and family functioning. The diagnosis of culture-bound syndrome was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The etiologies identified include psychosis in one out of two cases, as well as substance abuse, personality disorders, or gender dysphoria. Koro syndrome, observed mainly in Asia and North Africa (and therefore probably culturally determined), is the sudden onset of intense but reversible anxiety, associated with the fear that the penis (most often), vulva, or breasts will retract into the body (Elghazouani & Barrimi, 2018; Godfryd, 2015).…”
Section: Affective Disordersmentioning
confidence: 99%
“…The etiologies identified include psychosis in one out of two cases, as well as substance abuse, personality disorders, or gender dysphoria. Koro syndrome, observed mainly in Asia and North Africa (and therefore probably culturally determined), is the sudden onset of intense but reversible anxiety, associated with the fear that the penis (most often), vulva, or breasts will retract into the body (Elghazouani & Barrimi, 2018; Godfryd, 2015).…”
Section: Affective Disordersmentioning
confidence: 99%
“…26,27 Before the publication of the 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10), Koro-like symptoms tended to be subsumed under other diagnoses, for example, delusional disorder. [26][27][28] Furthermore, individuals with Koro symptoms often present without a clear history of psychosis or psychiatric illnesses. 29,30 Some studies, however, have demonstrated a clear link with psychosis and other psychiatric disorders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some take remedial actions by tying the penis with strings to an object, or getting others help (9). There are possible interactions between culture and psychopathology (8). The firm belief may take the form of a delusion, overvalued idea or an oedipal castration anxiety, especially when there is a male dominant cultural significance.…”
Section: Introductionmentioning
confidence: 99%